2015
DOI: 10.3389/fict.2015.00025
|View full text |Cite
|
Sign up to set email alerts
|

Brain–Computer Interfaces on Track to Home: Results of the Evaluation at Disabled End-Users’ Homes and Lessons Learnt

Abstract: The BackHome system is a multifunctional BCI system, the final outcome of a UserCentered Design approach, whose ambition is to move BCI systems from laboratories into the home of people in need for their independent home use. The paper presents the results of testing and evaluation of the BackHome system with end-users at their own homes. Results show moderate to good acceptance from end-users, caregivers, and therapists, which reported promising usability levels, good user satisfaction, and levels of control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Inexpensive technical solutions for EEG recordings (e.g OpenBCI) could be used with custom made headsets but do not provide easy solutions for non-professional users. As noted by Miralles et al [30] the price of BCI is currently the biggest restricting factor for large scale usability studies in the home environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inexpensive technical solutions for EEG recordings (e.g OpenBCI) could be used with custom made headsets but do not provide easy solutions for non-professional users. As noted by Miralles et al [30] the price of BCI is currently the biggest restricting factor for large scale usability studies in the home environment.…”
Section: Discussionmentioning
confidence: 99%
“…Brain computer interface usability studies with patients have been tested on several paradigms, including BCI spellers, painting, gaming, environmental control (smart homes) and cognitive rehabilitation [30, 31, 3443]. However, a very small number of these studies [30, 37, 40] have been performed in patients’ homes, and a trained specialist was often present. A “Back home” project, one of the largest of this kind, tested BCI designed for spelling, gaming and internet browsing on 9 patients at a hospital.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To allow the caregivers to set-up the soft- and hardware without expert supervision, the final Backhome prototype, consists of a graphical user interface that guides the caregivers through the steps necessary to set-up the system and enable the BCI user to control the various applications afterwards (Miralles et al, 2015b ). All the applications mentioned above (speller, web browser, multimedia player, Brain Painting, games for cognitive rehabilitation, switches for environmental control) were integrated into the prototype.…”
Section: Introductionmentioning
confidence: 99%
“…Assistive technologies aim to increase quality of life [36], reduce dependence on care giver [7] and reduce dependence on the long term care system [8]. Several studies have demonstrated the effectiveness in the use of environment control interfaces (ECI) for environment control or communication through voice commands [9], scan interfaces based on grid structure, eye tracking [10–12] or brain-computer interface (BCI) based on P300 [13], among others. These software platforms actively aid during the Activities of Daily Living (ADL) improving the independence both at home and outside.…”
Section: Introductionmentioning
confidence: 99%